Waspadai Penurunan Fungsi Ginjal pada Geriatri Melalui Deteksi Dini eGFR dan Serum Kreatinin Di Panti Werda Hana - Johan Johan; Alexander Halim Santos; Farell Christian Gunaidi; Geoffrey Christian Lo; Muhammad Farhan Pratama Susilo (Universitas 45 Surabaya, 2025)
Chronic kidney disease (CKD) is a major health concern frequently observed in the elderly population. Aging is associated with physiological changes that impact various organ systems, including a progressive decline in renal function due to a reduced number of functioning nephrons, which in turn leads to a gradual decrease in glomerular filtration rate (GFR). The Community Service Program (PKM) conducted at Panti Werdha Hana aimed to raise awareness among the elderly regarding the importance of early detection of kidney function impairment through serum creatinine measurement and estimation of eGFR. This initiative applied the Plan-Do-Check-Act (PDCA) approach, encompassing education on risk factors and laboratory testing. Among 76 participants, 19 individuals (25%) were identified with stage 5 CKD, 3 (3.95%) with stage 4, 6 (7.89%) with stage 3b, 17 (22.37%) with stage 3a, and 31 (40.79%) with stage 2 kidney function decline; additionally, 26 individuals (34.21%) had elevated creatinine levels. These findings underscore the critical importance of early detection to prevent CKD progression and associated complications, while also promoting improved quality of life in the elderly through timely intervention and continuous health educationKeywords: Chronic Kidney Disease, Early Detection, Elderly, Glomerular Filtration Rate, Serum Creatinine